AB0651 Preventive antituberculosis treatment before biologic agents initiating: frequency of prescription and tolerance in a sample of tunisian rheumatologic population. (23rd January 2014) - Saidane, O.; Dridi, L.; Mahmoud, I.; Sahli, H.; Tekaya, R.; Abdelmoula, L.; Chaabouni, L.; Zouari, R.
Abstract : Background: Treatment of latent tuberculosis (TB) is mandatory before biologic agents' instauration to prevent the risk of reactivation. Objectives: To assess frequency and reasons of TB chemoprophylaxis prescription in rheumatologic population and its tolerance. Methods: It is a retrospective monocentric study of medical records of patients receiving biologic agents (TNFalpha blockers and rituximab) who were hospitalized in Rheumatology department between 2005 and 2012. We included patients who received TB chemoprophylaxis. We noted epidemiologic characteristics, reasons of prescription, levels of alanine aminotransferase (ALAT) aspartate aminotransfere (ASAT, ) prethrombin time (PT) and gamma-glutamyl transferase (GGT) before and during treatment and when any side effect was observed. Results: Ninety tow prescriptions of biologic agents were reported in 84 patients. Among them, 11 (13%) received prophylaxis. Izoniazide 5mg/kg/day and Rifampicine 10mg/kg/day for 3 months (INH/RIF) were prescribed in all cases. Six patients presented with Rheumatoid arthritis (RA) and 5 with Spondylarthritis (SA). Age ranged from 34 to 76 with an average of 50 years. The mean disease duration was 10.3 years. The mean number of DMARDs previously received before introduction of biotherapy was 1.5 for patients with RA and 1 in patients with SA. The treatment by INH/RIF was prescribed in 11 cases because of intradermal tuberculin test positivity (n=8), an opacity on the chest radiography (n=1), QuantiFERON positivity (n=1) and because of positive culture of mycobacterium tuberculosis in urine (n=1) (in this case no urogenital TB was confirmed). Before INH/RIF instauration hepatic enzymes levels and TP were normal in all cases except one with hepatic steatosis (ALAT 2.7 times and GGT 4.2 times). Acetylating test was performed in all patients and INH dose was adapted based on. Biologic hepatotoxicity was noted in 3 cases. Cytolisis was noted in 1 case, increase of ALAT was 1.5 times and of ASAT 1, 2 times. Cholestasis was seen in 2 cases, average increase of GGT of 1.5 times. No variation in TP level was noted. No of this 3 patients was receiving methotrexate or sulfasalazine. No changes in liver biologic tests was observed in the patient who had hepatic steatosis. Gastrointestinal side effects (nausea and abdominal pain) was seen in one case. No haematological, cataneous, neurological or ophthalmologic side effect was described. We did not need a therapeutic modification because the intensity of the side effects was mild. Conclusions: Despite being a TB endemic country, prevalence of chemoprophylaxis prescription in Tunisian rheumatologic population is relatively low. Occurred side effects were always benign. Disclosure of Interest: None Declared